Early phase evaluation of SQ109 alone and in combination with rifampicin in pulmonary TB patients. (27th January 2015) - Heinrich, Norbert; Dawson, Rodney; du Bois, Jeannine; Narunsky, Kim; Horwith, Gary; Phipps, Andrew J.; Nacy, Carol A.; Aarnoutse, Rob E.; Boeree, Martin J.; Gillespie, Stephen H.; Venter, Amour; Henne, Sonja; et al.
Abstract: Objectives: SQ109, an asymmetrical diamine, is a novel anti-TB drug candidate. This first study in patients was done to determine safety, tolerability, pharmacokinetics and bacteriological effect of different doses of SQ109 alone and in combination with rifampicin when administered over 14 days. Patients and methods: Smear-positive pulmonary TB patients were randomized into six groups of 15 to receive once-daily oral treatment with 75, 150 or 300 mg of SQ109, rifampicin (10 mg/kg body weight), rifampicin plus 150 mg of SQ109, or rifampicin plus 300 mg of SQ109 for 14 days. Patients were hospitalized for supervised treatment, regular clinical, biochemical and electrocardiographic safety assessments, pharmacokinetic profiling and daily overnight sputum collection. Results: SQ109 was safe and generally well tolerated. Mild to moderate dose-dependent gastrointestinal complaints were the most frequent adverse events. No relevant QT prolongation was noted. Maximum SQ109 plasma concentrations were lower than MICs. Exposure to SQ109 (AUC0–24 ) increased by drug accumulation upon repeated administration in the SQ109 monotherapy groups. Co-administration of SQ109 150 mg with rifampicin resulted in decreasing SQ109 exposures from day 1 to day 14. A higher (300 mg) dose of SQ109 largely outweighed the evolving inductive effect of rifampicin. The daily fall in log cfu/mL of sputum (95% CI) was 0.093 (0.126–0.059) with rifampicin, 0.133 (0.166–0.100) with rifampicin plus 150 mg of SQ109 and 0.089 (0.121–0.057) with rifampicin plus 300 mg of SQ109. Treatments with SQ109 alone showed no significant activity. Conclusions: SQ109 alone or with rifampicin was safe over 14 days. Upon co-administration with rifampicin, 300 mg of SQ109 yielded a higher exposure than the 150 mg dose. SQ109 did not appear to be active alone or to enhance the activity of rifampicin during the 14 days of treatment.